Quasi-1D hyperbranched WO3 nanostructures for low-voltage photoelectrochemical water splitting1. Issue 11 (21st March 2015) - Balandeh, Mehrdad; Mezzetti, Alessandro; Tacca, Alessandra; Leonardi, Silvia; Marra, Gianluigi; Divitini, Giorgio; Ducati, Caterina; Meda, Laura; Di Fonzo, Fabio
<x xml:space="preserve">Abstract</x> Arrays of hyperbranched mesostructures self-assembled from the gas phase display a decreased overpotential for the water oxidation reaction.